Consumption of fallen stock: A risk assessment - Simpson, A. (Royal Veterinary College, 2015)
Consumption of fallen stock could be an important route for zoonotic infections to enter human populations. Qualitative and Quantitative risk assessments were performed in order to determine the risk to human health via consumption of fallen stock and identify potential methods for mitigating risk. After initial hazard identification (disease selection) three pathogens were chosen for assessment; two for qualitative and one for quantitative. Influenza A (H5N1) and the prion causing Bovine Spongiform Encephalopathy (BSE) and variant Creutzfeldt-Jakob Disease (vCJD) were chosen for qualitative assessment. Bacillus anthracis was chosen for quantitative assessment. The qualitative assessments were designed to answer the question: “In the scenario of a disease outbreak amongst livestock, what is the risk of one or more human cases (and deaths) occurring due to the preparation and consumption of fallen stock”. The quantitative model was designed to provide probability of infection and subsequent death with Gastro-Intestinal (GI) Anthrax occurring in individuals consuming meat from fallen cattle, whilst also predicting the number of cases and deaths occurring in Western Province (WP), Zambia. The Risk from H5N1 was determined to be “low” to “medium”, and the risk from the prion causing BSE was “very low”. Results from the quantitative assessment suggest that mean individual risk of infection with GI Anthrax is less than 1 in 10,000,00 but that the probability of infection given consumption of an infected carcass was 1 in 4695. The mean probability of at least one case of GI Anthrax occurring in WP was 1 in 9. Sensitivity analysis of the quantitative model suggested that the ingested dose of B. anthracis was the most important determinant of disease, and that the ingested dose was most affected by spore reduction during cooking. Qualitative assessment also suggested that risk could be reduced by taking precautions when preparing and consuming meat from infected animals including careful butchery and ensuring meat is properly cooked. This brief assessment has begun to describe the risk to human health from consumption of fallen stock, and has provided insights which could be taken forward in to future work.